PENTINGNYA PELAKSANAAN PLANT LAY OUT YANG TEPAT UNTUK MENUNJANG KELANCARAN PROSES PRODUKSI PADA PT MEGA KHARISMA MAKMUR (MKM) KABEL JAWILAN-SERANG - Rina Martiana; Aman Aman (The Asia Pacific Journal Of Management Studies, 2018)
Decision of the design layout (plan layout) are important decisions that determine the production capacity of an operation in the long term and setting thelayout engine should be considered for the creation of effectiveness and efficiency when performing production so smooth production process will go smoothly, as for the purpose of this study is 1) to know the process of production of PT MKM Kabel, 2) to find out how the implementation of plant layout in PT MKM kabel, 3) pinpoint how important the implementation of the factory layout for a smooth production process at PT MKM Kabel. The analytical method used is a qualitative method. During the research data collection techniques used were observation, interviews and documentation. Results of the study is the implementation of the plant layout to a smooth production process is very important in a company, the company has been using the layout engine, but in practice the layout engine at the company MKM Kabel has not been especially well can be seen between the distance from the machine strending tothe extruder is too far due to limited land in companies that do not allow it to be moved sehinggakan inhibit the production process and leakage problems that occur in the company should also be diperhatkan so that the production process runs smoothly and will be optimized.